Willingness to use pre-exposure prophylaxis for HIV prevention among men who have sex with men in Malaysia: Findings from an online survey - Lim, S.H.; Mburu, G.; Bourne, A.; Pang, J.; Wickersham, J.A.; Wei, C.K.T.; Yee, I.A.; Wang, B.; Cassolato, M.; Azwa, I. (Public Library of Science, 2017)
Objective We examined willingness to use pre-exposure prophylaxis (PrEP) for HIV prevention among men who have sex with men (MSM) in Malaysia. Methods An online survey of 990 MSM was conducted between March and April 2016. Eligibility criteria included being biological male, Malaysian citizen, 18 years of age or above, identifying as MSM, and being HIV negative or unknown status. Participants' demographics, sexual and drug use behaviors, attitudes towards PrEP, and preferences regarding future access to PrEP were collected. Bivariate analysis and logistic regression were performed to determine factors associated with willingness to use PrEP. Results Fewer than half of participants (44%) knew about PrEP before completing the survey. Overall, 39% of the sample were willing to take PrEP. Multivariate logistic regression indicated that Malay men (AOR: 1.73, 95% CI:1.12, 2.70), having 2 or more male anal sex partners in the past 6 months (AOR: 1.98, 95% CI: 1.29, 3.05), previous knowledge of PrEP (AOR: 1.40, 95%CI: 1.06, 1.86), lack of confidence in practising safer sex (AOR: 1.36, 95% CI: 1.02, 1.81), and having ever paid for sex with a male partner (AOR: 1.39, 95% CI: 1.01, 1.91) were independently associated with greater willingness to use PrEP, while men who identified as heterosexual were less willing to use PrEP (AOR, 0.36, 95% CI: 0.13, 0.97). Majority of participants preferred to access PrEP at affordable cost below 100 Malaysian Ringgit (USD25) per month from community based organisations followed by private or government hospitals. Conclusions Overall, MSM in Malaysia reported a relatively low level of willingness to use PrEP, although willingness was higher among those previously aware of PrEP. There is a need to provide PrEP at affordable cost, increase demand and awareness of PrEP, and to provide access to this preventative medication via diverse, integrated and tailored sexual health services.